Penerapan Prinsip Keadilan Dalam Hukum Islam: Analisis Konsep Ijtihad Khalifah Umar Bin Khattab - Meilani M; Fatmawati F; Lomba Sultan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Umar bin Khattab was the second caliph of Khulafa' al-Rosyidin after Abu Bakr al-Shiddiq. He was known as an honest, firm and brave caliph. He not only showed his courage on the battlefield through several expansions he carried out to several regions such as Persia, Syria, Africa and several other cities. However, he also dared to make ijtihad in deciding a legal case which was often considered by the ulama to be contrary to the concepts of the Koran and Hadith. The thoughts or results of Umar bin Khattab's ijtihad are also identical to his progressive law. Ijtihad 'Umar ibn al-Khaá¹á¹Äb and Progressive law have several characteristics in common, namely that they both state that law exists for the good of humans, require legal reform, and recognize the role of human behavior. in the law. However, the two have differences in terms of understanding and determining benefits. The concept of justice adopted by Umar bin Khattab as one of the leading caliphs in Islamic history, still has relevance in the modern context. Although Umar bn Khattab's concept of justice can be applied in a modern context, it is important to understand that historical and cultural contexts change over time, and their interpretation and application may vary.